Anthraquinones and Xanthones from Cratoxylum glaucum (Guttiferae) - Ee, Gwendoline Cheng Lian; Kua, Audrey Siew May; Rahmani, Mawardi (Universiti Putra Malaysia, 2007)
In a continuing search for xanthones and quinones from the Guttifere family, we decided to look at the genus Crotoxylum. A detailed chemical study on Cratoxylum glaucum has led to the isolation of two triterpenoids, friedelin (1) and stigmasterol 9(2), two anthraquinones 1,8-dihydroxy-6-menthoxyanthraquinone (3) and vismiaquinone (4) and one xanthone dimenthymangostin (5). These compounds were identified using the 1D and 2D NMR spectroscopy. This is the first report done on the chemistry of Cratoxylum glaucum.